Between a rock and a hard place: The impact of the professionalization of the role of the teaching assistant in mainstream school physical education in the United Kingdom - Farr, Jackie (Sport in society, 2018)
National surveys of the role of the teaching assistant (TA) in the United Kingdom and the para-educator in the USA have explored and revealed trends in the recruitment, training, deployment and perception of their roles. Recent subject-specific research in the UK has further considered how TAs construct their role when supporting disabled pupils in a specific curriculum subject in a mainstream setting. In light of the implementation of a new code of practice in England from 2014 which changes the way in which a child with special educational needs and disabilities is supported in schools and beyond, this paper explores the roles of TAs working in secondary mainstream schools in the UK who are employed to support disabled children in Physical Education. It considers the way in which the role of the TA has evolved and developed in England following 'Workforce Reform' in 2003 and draws on research and literature from a number of sources to explain and update the nomenclature and responsibilities of the para-professional who seems to work 'subdoceo' (from the Latin meaning 'to teach as an assistant'). It is an attempt to consolidate what we know about these roles in a specific subject and to reaffirm the trends identified from the existing small body of work in the UK. In doing so, this paper aims to provide a platform for further research but will also remind teachers of their role in ensuring that their collaboration with and deployment of these 'paraprofessionals' is paramount to the best interests of the child. (Autor).